Fabrication and characterization of novel starch-grafted poly l-lactic acid/montmorillonite organoclay nanocomposites. (10th February 2016) - Eğri, Özlem; Salimi, Kouroush; Eğri, Sinan; Pişkin, Erhan; Rzayev, Zakir M.O.
Highlights: Poly(l -lactic acid)- g -starch layered silicate nanocomposites were fabricated. Preintercalated LA-MMT organoclay exhibit dual functions as catalyst and compatibilizer. LA-MMT organoclay accelerated in situ graft copolymerization via esterification of LA. The obtained results confirmed the intercalation/exfoliation of silicate galleries. Highly exfoliation of clay and graft copolymerization led to high thermal stability of NCPs. Abstract: In this work, poly(l -lactic acid)- g -starch layered silicate nanocomposites (NCs) (PLLA- g -starch/MMT) were fabricated by intercalative bulk graft copolymerization of LA with starch, in the presence of either stannous octoate acting as a catalyst or LA-MMT organoclay acting as a cocatalyst-nanofiller. This procedure was performed inside a custom vacuum micro-reactor. To better understand the graft copolymerization mechanism, in situ processing types, interfacial interactions and nanostructure formation of PLLA- g -starch/MMT NCs, methods such as FT-IR, XRD, 1 H NMR, 13 C CP/MAS-NMR, DSC/TGA, TEM and SEM were utilized. The morphology and thermal behaviors of nanocomposites were found to be strongly dependent on the loading mass fraction of LA-MMT within the nanocomposite structure and the type of in situ processing such as interfacial, physical and chemical interactions. Preintercalated LA-MMT organoclay exhibited dual functions. It demonstrated the ability to act as a catalyst, essentially accelerating in situ graft copolymerization via esterification of LA carboxyl groups with hydroxyl groups of starch macromolecules, whilst also acting as a nananofiller-compatibilizer.